PREDICTORS OF CONTINUOUS HOSPITAL STAY IN ADULT PATIENTS WITH ACQUIRED VALVULAR DISEASE, OPERATED WITH HYPOTHERMIC AND NORMOTHERMIC CARDIOPULMONARY BYPASS - D. G. Shakhin; V. A. Shmyrev; S. M. Efremov; D. N. Ponomarev; G. B. Moroz; I. A. Kornilov; A. N. Shilova; V. N. Lomivorotov; O. V. Kuleshov; M. A. Novikov; V. V. Lomivorotov (Вестник анестезиологии и реаниматологии, 2017)
Goal of the study: to identify the predictors of continuous hospital stay in adult patients with acquired valvular disease, operated with hypothermic and normothermic cardiopulmonary bypass due definitive repair of the disease. Materials and methods: 140 patients who had surgical treatment of acquired valvular disease with the use of cardiopulmonary bypass were randomly divided into two similar groups where hypothermic and normothermic cardiopulmonary bypasses were used. Peri-operative concentration of NT-proBNP, clinical course of the post-operative period, hospital morbidly and mortality were assessed. Results. No confident difference was observed in the changes of NT-proBNP in the groups, what could provide the evidence of the similar effects of both hypothermic and normothermic cardiopulmonary bypasses on integrative functional rates of cardiovascular system. However it was noted that increase of NT-proBNP plasma concentration during first 24 hours after the surgery, as well as age, chronic obstructive pulmonary disease (COPD), maximum degree of chronic cardiac failure (CCF), duration of artificial pulmonary ventilation (APV), episodes of atrial fibrillation (AF) in the post-operative period were the predictors of continuous hospital stay Conclusion. The degree of the increase in post-operative level of NT-proBNP does not depend on the perfusion temperature. NT-proBNP plasma concentration during first 24 hours after the surgery, age, COPD, maximum degree of CCF, duration of APV, episodes of AF in the post-operative period are independent predictors of continuous hospital stay.